Fatores associados à experiência de cárie dentária em escolares da rede pública de um município de pequeno porte do Nordeste brasileiro (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2017)
Factors associated with the experience of dental caries in public schools at a small city in the Northeast of Brazil